The contributions of cartography and iconography to the study of urban transformation in colonial Rio de Janeiro - Braida, Frederico (National Journal of City Management, 2021)
This paper regards Brazilian colonial cartography and iconography, especially the ones related to Rio de Janeiro. It aims to establish said cartographic material as a solid record for researches on Rio de Janeiro’s early urbanization. In order to achieve that, this study relies on qualitative research and it has an exploratory character. Furthermore, this is both bibliographic and iconographic research regarding the data collection. At first, there are considerations related to overseas exploration, the “Discovery of Brazil,” and the founding of São Sebastião do Rio de Janeiro. Then, the article discusses the meaning of “cartography.” Finally, the present study advocates for the relevance of charts, plans, and maps concerning colonial Brazilian cities as they provide aid in comprehending the Rio de Janeiro we live in today.